ASSESSMENT OF OCCUPATIONAL STRESS AND JOB SATISFACTION AMONG SCHOOL TEACHERS IN SELECTED HIGHER SECONDARY SCHOOLS OF MURSHIDABAD, WEST BENGAL - Bhattacharjya, Sukonna; Choudhuri, Moitreyee (International Journal of Research -GRANTHAALAYAH, 2024)
Introduction: Occupational stress among teachers results from the working conditions. Stressed out teachers cannot work effectively. Their motivation and job satisfaction are lower, and they exhibit undesirable behaviours. Aim: This study aims to find out school teachers' degree of job satisfaction and occupational stress, to identify correlation between work-related stress, job satisfaction, and association between occupational stress with the selected sociodemographic aspects. Method: In order to ascertain occupational stress and job satisfaction among school teachers in the contemporary, demanding world, the researcher carried out a descriptive survey research on assessment of occupational stress and job satisfaction among teachers in selected higher secondary schools of Murshidabad, West Bengal. The method of non-probability convenience sampling was used to choose 120 school teachers working in selected higher secondary schools of Murshidabad, West Bengal. A semi-structured questionnaire, the Teachers Occupational Stress Scale designed by Sajid Jamal and Abdul Raheem, and the Job Satisfaction Survey created by Paul E. Spector, were used to gather the data. Result: The study result showed that majority of school teachers (92.5%) had moderate/average degree of occupational stress. Most of the school teachers (81.66%) had ambivalent level of job satisfaction. The study also revealed occupational stress and job satisfaction of school teachers’ have a weakly negative correlation which was significant. A chi-square test indicated a significant association between the age of a school teacher and occupational stress. The study has implications for Nursing Research, Nursing Administration, Nursing Practice, and Nursing education and it is recommended for future research study.